2020
DOI: 10.1111/srt.12887
|View full text |Cite
|
Sign up to set email alerts
|

Biometric changes of skin parameters in using of microneedling fractional radiofrequency for skin tightening and rejuvenation facial

Abstract: Background: Fractional radiofrequency (RF) has been used for skin rejuvenation and tightening by dermatologists and cosmetic surgeons in recent years. Methods: Twenty female patients (mean age of 51.9 years) with Fitzpatrick III to VI skin phototypes who desired to undergo skin lift/tightening received six sessions of fractional microneedle RF treatment and were assessed at baseline and then 3 months after the last session for biometric characteristics using a Colorimeter, Visioface 1000D, Tewameter, Cutometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 10 publications
0
43
0
4
Order By: Relevance
“…This analysis indicates that when using the HFUS technique for this purpose, antiaging treatments are expected to promote increased dermal echogenicity, which in turn is related to increased collagen content and dermal redensification. 48 Crisan et al (2015) showed that topically applied vitamin C is highly efficient as a rejuvenation therapy, inducing significant collagen synthesis in all age groups studied through the HFUS technique.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis indicates that when using the HFUS technique for this purpose, antiaging treatments are expected to promote increased dermal echogenicity, which in turn is related to increased collagen content and dermal redensification. 48 Crisan et al (2015) showed that topically applied vitamin C is highly efficient as a rejuvenation therapy, inducing significant collagen synthesis in all age groups studied through the HFUS technique.…”
mentioning
confidence: 99%
“…22 One of the anti-aging strategies used is the fractional radiofrequency (RF) procedure for skin rejuvenation performed by dermatologists and plastic surgeons. 48 In a study developed by…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A aplicação de RF pode ser realizada entre uma ou em várias sessões, depende do dispositivo e dos indivíduos que irão receber o tratamento. Nilforoushzadeh et al, (2020) ideal, estimam-se, e devem estar em conformidade com a diversidade de protocolos, equipamentos terapêuticos e etnia de cada indivíduo (GORGU et al,2019).…”
Section: Métodounclassified
“…Journal of Health Review, Curitiba, v.4, n.6, p. 25606-25616 nov./dec. 2021(NILFOROUSHZADEH et al, 2020;SERDAR et al, 2019;ZHANG et al, 2018;GOLD et al, 2016). A literatura explica esses resultados por meio de achados histológicos, dado que, sendo minimamente invasiva, a radiofrequência microagulhada fornece corrente para a derme profunda e cria uma zona térmica controlada, reservando a epiderme.…”
unclassified